Uptake and Inactivation of Thrombin on Rabbit Aortic Endothelium Studied with Two Different Substrates - Swedenborg, Jesper; Dryjski, Maciej; Frebelius, Siw; Olsson, Per (Thrombosis and Haemostasis, 1985)
The endothelium is an important compartment for uptake and inhibition of thrombin. The amount of enzymatically active bound thrombin can be detected with both small synthetic substrates and with aid of fibrinogen as substrate. The present study was designed to investigate the relation between endothelially bound thrombin with amidolytic activity towards a synthetic substrate (S-2238) and thrombin capable of converting fibrinogen by measuring generation of fibrinopeptide A (FPA). The luminal surfaces of rabbit aortae (2 cm2) were exposed in vitro to thrombin (0.625-5.0 NIH units/ml). Thrombin disappeared from the solution and a certain fraction was recovered on the surface. There was a linear relationship between the amount of thrombin on the surface and the concentration of thrombin in the incubation mixture. Approximately one third of the thrombin measured with S-2238 was also able to cleave fibrinogen. After incubation with defibrinogenated plasma almost total inhibition of fibrinogen splitting activity occurred within 30 sec. The inhibition of the amidolytic activity was less complete. When endothelially bound thrombin was exposed to plasma much less FPA was generated than in a fibrinogen solution. A minor fraction of endothelially bound thrombin was inhibited also upon incubation with Tyrode without recovery of any enzymatic activity in the solution. The results indicate that a fraction of thrombin bound to the endothelium has retained enzymatic activity and that a fraction of the enzymatically active thrombin is capable of converting fibrinogen. Inhibition of thrombin enzymatic activity occurs rapidly upon exposure to plasma. The endothelium itself has a minor inhibitory effect also in the absence of plasma. Thrombin with retained fibrinogen splitting activity may contribute to thrombotic events particularly if plasma inhibitors are insufficient. Thrombin with activity towards fibrinogen could be bound to GAG:s whereas thrombin active towards S-2238 could be bound to GAGrs TM or possibly other receptors.
Keywords: Endothelium; Thrombin; Chromogenic substrate; Fibrinogen